Characterization of acute TLR-7 agonist-induced hemorrhagic myocarditis in mice by multiparametric quantitative cardiac magnetic resonance imaging. - Baxan,N; Papanikolaou,A; Salles-Crawley,I; Lota,A; Chowdhury,R; Dubois,O; Branca,J; Hasham,MG; Rosenthal,N; Prasad,SK; Zhao,L; Harding,SE; et al. (Dis Model Mech, 2019)
Hemorrhagic myocarditis is a potentially fatal complication of excessive levels of systemic inflammation. It has been reported in viral infection, but is also possible in systemic autoimmunity. Epicutaneous treatment of mice with the Toll-like receptor 7 (TLR-7) agonist Resiquimod induces auto-antibodies and systemic tissue damage, including in the heart, and is used as an inducible mouse model of systemic lupus erythematosus (SLE). Here, we show that overactivation of the TLR-7 pathway of viral recognition by Resiquimod treatment of CFN mice induces severe thrombocytopenia and internal bleeding, which manifests most prominently as hemorrhagic myocarditis. We optimized a cardiac magnetic resonance (CMR) tissue mapping approach for the in vivo detection of diffuse infiltration, fibrosis and hemorrhages using a combination of T1, T2 and T2 relaxation times, and compared results with ex vivo histopathology of cardiac sections corresponding to CMR tissue maps. This allowed detailed correlation between in vivo CMR parameters and ex vivo histopathology, and confirmed the need to include T2 measurements to detect tissue iron for accurate interpretation of pathology associated with CMR parameter changes. In summary, we provide detailed histological and in vivo imaging-based characterization of acute hemorrhagic myocarditis as an acute cardiac complication in the mouse model of Resiquimod-induced SLE, and a refined CMR protocol to allow non-invasive longitudinal in vivo studies of heart involvement in acute inflammation. We propose that adding T2 mapping to CMR protocols for myocarditis diagnosis improves diagnostic sensitivity and interpretation of disease mechanisms.This article has an associated First Person interview with the first author of the paper.